Field and laboratory evaluation of the long-term effect of various organic fertilizers on sandy soil - József Tibor Aranyos; Liyana Zulkipli; Marianna Makádi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Recent trends in land use and the effects of climate change resulted in the decline of organic matter content of the soils. Since crop management systems play an important role in soil carbon sequestration, therefore our aim was to determine the long-term effects of different organic fertilizers on soil respiration and its driving factors.Method: The research work was carried out in two long-term experiments on sandy soil. The field and laboratory measurements of soil respiration were done in fallow, farmyard manure, farmyard manure + fertilizer, green manure and in sewage sludge compost (18 and 27 t ha-1) treatments. In addition, soil physical-chemical parameters were measured for complex evaluation.Results: The results of laboratory and field soil respiration measurements were usually consistent with each other. The most intensive soil respiration was measured in sewage sludge compost treatments and in farmyard manure with NPK. In these treatments, the organic matter input and the positive changes in the physical and chemical properties of sandy soil stimulated the soil life, which resulted in more intensive soil respiration and enzyme activities. According to the results of correlation analysis the soil respiration was significantly influenced by the organic matter content, pH and moisture content of the soil.Conclusion: This study indicated the importance of replenishing the soil with organic matter, which can contribute to the maintenance of soil quality. In addition, the application of sewage sludge compost can be well utilized in agriculture for nutrient supply and improving carbon sequestration of sandy soil.